Kawasaki Disease Associated with Streptococcal Infection and Facial Nerve Palsy: A Case Report - Abdullahi Musa; Abiola A. Olorukooba; Sakinatu M. Abdullahi; Sani Musa; Hauwa U. Makarfi (Ntec Specialist, 2022)
Background: Kawasaki disease (mucocutaneous lymph node syndrome), an acute febrile vasculitis of childhood that affects medium and small-sized arteries, is uncommonly reported in the West African subregion. Its diagnosis relies on the presence of a constellation of clinical signs which could mimic or coexist with infectious viral or bacterial agents, thereby requiring a high index of suspicion. Case presentation: We report a two-year, ten months-old boy who presented with prolonged high-grade fever for over 3 three weeks; non-purulent conjunctivitis, unilateral cervical lymphadenopathy, cracked lips, reddish tongue, diffuse oedema, erythema of his palms and soles; skin desquamation over the tips of his digits and left-sided facial nerve palsy. He had leukocytosis, thrombocytopenia, and elevated inflammatory markers. Throat swab yielded Streptococcus pyogenes species; however, serial echocardiography was unrevealing. He was managed with aspirin, steroids, bed rest, and antibiotics (based on culture sensitivity), but intravenous immunoglobulin (IVIG) was not readily available and therefore was not administered. His inpatient clinical course showed fever persisting into the second week of inpatient management that gradually became undulating by the third week before lysing. Conclusion: The rare complication of facial nerve palsy is highlighted, while the evidence for acute bacterial infection posed further diagnostic challenges in this child with clinical features of Kawasaki disease. The unavailability of IVIG also portends a prolonged course for the acute stages, which are largely unresponsive to antipyretics and antibiotics. The importance of longterm follow-up for potential coronary artery aneurysms in the face of risk factors is further emphasized.